2016
DOI: 10.1515/phys-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bonding study of photoexcited 4-nitro-1,8-naphthalimide in hydrogen-donating solvents

Abstract: Abstract:The solute-solvent interactions of 4-nitro-1,8-naphthalimide (4NNI) as a hydrogen bond acceptor in hydrogen donating methanol (MeOH) solvent in electronic excited states were investigated by means of the timedependent density functional theory(TDDFT). We calculated the S 0 state geometry optimizations, electronic transition energies and corresponding oscillation strengths of the low-lying electronically excited states for the isolated 4NNi and hydrogen-bonded 4NNi-(MeOH) 1,4 complexes using the densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…The experiments also showed that the interactions between the ImNIDs and the presence of a polar compound (DMSO) affected the emission properties. Based on the above considerations, it can be concluded that the ability of 1,8-naphthalimide derivatives to form intermolecular interactions might significantly affect the photophysical properties of the system, which has also been considered in other works [40,41].…”
Section: Absorption and Emission Investigationsmentioning
confidence: 85%
“…The experiments also showed that the interactions between the ImNIDs and the presence of a polar compound (DMSO) affected the emission properties. Based on the above considerations, it can be concluded that the ability of 1,8-naphthalimide derivatives to form intermolecular interactions might significantly affect the photophysical properties of the system, which has also been considered in other works [40,41].…”
Section: Absorption and Emission Investigationsmentioning
confidence: 85%